Genre analysis of dissertation acknowledgements: a comparative study across contexts - Wenhsien, Yang (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
Compared to its counterparts, i.e. China and Honk Kong, research on generic structures of acknowledgements in dissertations in Taiwan is understudied. To fill the gap, this study examined 120 MA and PhD dissertation acknowledgements written by Taiwanese Chinese-speaking writers in terms of generic structure and linguistic features in order to investigate whether differences exist within one single/similar culture, and to explore the possible causes of the differences. The results suggest that the authors generally followed the same three-tier structure of writing dissertation acknowledgements as their counterparts. However, contextual factors such as academic, socio-cultural or geographical differences among three settings also affected their construction of moves and choices of linguistic elements. It was found that the rhetorical language in our corpus was relatively direct, emotional, and definite. Moreover, a new step called ‘Making a Confession’, which was not reported in the other two settings, was identified in the study. Suggestions for further investigations and pedagogical implications are offered.